High HIV Detection in a Tertiary Facility in Liberia: Implications and Opportunities - Onyema Ogbuagu; Ian Wachekwa; Faiza Yasin; Cecilia Nuta; Sean Donato; Julia Toomey; Mukhtar Adeiza; Lydia Aoun Barakat (Ubiquity Press, 2021)
Background: HIV/AIDS remains one of the world's most significant public health challenges; sub-Saharan Africa accounts for 71% of the global burden of HIV. Testing for HIV is pivotal to achieving UNAIDS 95-95-95 target towards bringing an end to the epidemic. Objective: The study assessed five-year HIV testing data from the largest tertiary hospital in Monrovia, Liberia and highlights risk groups that would benefit from targeted testing and prevention interventions. Methods: This was a single-center academic hospital-based retrospective analysis of HIV testing data from January 2014 to December 2018 obtained from all testing sites at John F. Kennedy Medical Center in Monrovia, Liberia. Pooled HIV testing data during the study period were analyzed using descriptive statistics and stratified by age, gender and pregnancy status. Annual diagnoses rates were reported as proportion of individuals tested within a specified category (age [<15 years, age 15-24 years and >=25 years], gender, and pregnancy status) that had a positive HIV test. Five-year trends were analyzed. Results: Over the study period, 41,343 non-pregnant individuals were screened for HIV. In addition, the antenatal clinic performed 24,913 tests. Of non-pregnant individuals tested, 4,066 (10%) were diagnosed with HIV ranging from 7% (909/12821) in 2018 to 13% (678/5079) in 2014. Case detection rates for individuals aged 15-24 were 7%, 5%, 4%, 6% and 3% for years 2014, 2015, 2016, 2017 and 2018 respectively. Annually, 2-3% of all pregnant women tested were diagnosed with HIV. While HIV detection rates decreased over time overall, children less than 15 years of age showed an annual increase from 6.7% in 2014 to 12.3% in 2018. Conclusion: A large five-year dataset from the largest tertiary facility in Liberia shows broad HIV detection rates that are much higher than national prevalence estimates. Ramping up HIV testing and prevention interventions including pre-exposure prophylaxis are sorely needed.